CLARA KARYA SENO GUMIRA AJIDARMA DALAM KAJIAN STILISTIKA - Christine Resnitriwati, . (Faculty of Humanities, Diponegoro University, 2014)
Abstract People can express their feelings by using several ways –orally or in written.Orally means when they speak their feelings directly in front of other people, but when they express their feelings by writing them down in a novel, plag, poem or letter, we call it as in written. Seno Gumira Ajidarma expressed his feeling in Clara in written. He protested the humiliation of Chinese women in 1998 by unknown people in Indonesia.The purpose in this paper is to analyze the way how Seno expressed his feeling in Clara.The writen used stylistic method to understand what the author will say in that story, the exthetic elements and special effects that we can get in Clara by using this method.The results show that the stylistic method using in Clara can express clearly the author’s ideology about the misery of Chinese woman named Clara who was raped brutally in Mei 1998. Keywords: Cina, perkosa, gaya bunyi, gaya kata, gaya kalimat